New Analysis of the OH⊖ Conductance Mechanism in Aqueous Solution - Horst Herrmann; Hermann Gerhard Hertz; Richard Maurer (CHIMIA)
It is shown that the commonly used schematic representation of the OH⊖ conductance mechanism in aqueous solution is not the analogue of the corresponding diagrams for the H⊕ ion. The experimental finding of only comparatively slow motion in these solutions prompted us to derive a relation between the equivalent conductance, the OH⊖ drift velocity, and the parameters of OH⊖ exchange of the water molecules. With some remarks the connection to the analogous treatment referring to the H⊕ conductance is outlined.